Structural Change in Production Networks and Economic Growth - Paul Gaggl; Aspen Gorry; Christian vom Lehn (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies structural change in production networks for intermediate inputs (input-output network) and new capital (investment network). For each network, we document a declining fraction of production by goods sectors and a rising fraction of production by services sectors. We develop a multisector growth model that admits structural change in production networks along the balanced growth path to study these trends. Disaggregated final expenditure data reveal that inputs to investment production are substitutes, rather than strong complements as suggested by existing work. Hence, resources endogenously reallocate toward the fastest growing producers of investment. Growth accounting exercises demonstrate that investment-specific technical change has risen in importance for aggregate U.S. growth over time, with 20-25% of aggregate growth after 2000 stemming from reallocation induced by structural change. At the same time, productivity growth within the input-output network has stagnated, contributing to the recent slowdown in aggregate growth.
Keywords: E23; O14; O40; O41; 330; structural change; input-output network; investment network; economic growth; technical change; balanced growth